Developing an Integrated Risk Management and Circular Economy Model for Enhancing Resilience and Sustainable Competitiveness of Agroindustrial SMEs - Yan Herdianzah; Riska Iva Riana; A Dwi Wahyuni P; Anisa Sye; Muh. Rendy Juhari (Journal of Industrial System Engineering and Management, 2026)
This study aims to develop and validate an integrated Risk Management (RM) and Circular Economy (CE) model for enhancing SME Resilience (SR) and Sustainable Competitiveness (SC) in agroindustrial SMEs. The research employed a mixed-methods approach involving observations, interviews, Focus Group Discussions (FGD), and questionnaire surveys conducted on 157 respondents from agroindustrial SMEs producing banana chips in East Luwu, Indonesia. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results revealed that RM positively affects SR with a path coefficient of 0.384, while CE demonstrated the strongest influence on SR with a coefficient of 0.451. Furthermore, SR significantly influenced SC with a coefficient value of 0.612. Mediation analysis confirmed that SR significantly mediates the relationships between RM and SC (0.235) as well as CE and SC (0.276). The findings indicate that integrated risk management and circular economy practices improve operational adaptability, sustainability, and long-term competitiveness in agroindustrial SMEs.